Analysis of Influencing Factors for High-risk Human Papillomavirus Infection - WANG Xiaodan; ZHANG Zhan; LIU Zhaohui (Xiehe Yixue Zazhi, 2023)
Objective  To investigate the relevant risk factors of high-risk human papillomavirus(HR-HPV) infection.  Methods  From October 2020 to January 2021, the cases of positive HR-HPV test were selected as the infection group, and the cases of negative HR-HPV test were selected as the control group. Both groups of patients filled in self-designed 'survey of HR-HPV infection-related factors' in order to explore the relevant risk factors.  Results  A total of 125 patients in the infection group and 53 patients in the control group were included. Univariate analysis showed that there were statistically significant differences between the two groups in the following factors: unemployed or low socioeconomic status, vulva cleaning with lotion, high frequency of vaginal irrigation, homosexual orientation, production number, history of vaginitis, large amount of vaginal secretions, abnormal characteristics of vaginal secretion and chlamydia trachomatis infection(all P < 0.05). Logistic regression analysis showed that production number(OR=5.106, 95% CI: 1.521-17.145, P=0.008), previous history of vaginitis (OR=3.910, 95% CI: 1.167~13.099, P=0.027) and abnormal vaginal secretion (OR=758.313, 95% CI: 58.151~9888.714, P < 0.001) were risk factors for HR-HPV infection. In addition, the habit of using lotion to clean the vulva or vagina(OR=2.004), homosexual orientation (OR=13.972), and chlamydia trachomatis infection (OR=15.058) all showed a strong association with HR-HPV, but due to the small number of samples in the control group, no conclusions with statistical significance were drawn.  Conclusions  HR-HPV papillomavirus infection is associated with a variety of factors. Production number, history of vaginitis and abnormal characteristics of vaginal secretion are risk factors for HR-HPV infection. It is therefore recommended to pay attention to the characteristics of vaginal secretions, and timely seek medical treatment if there is any abnormality. If possible, cervical HR-HPV screening should be added to the vaginal microecological examination. If there are reproductive tract inflammatory diseases, it should be treated in time, so as to prevent HR-HPV infection from many aspects and reduce the risk of continuing infection of HR-HPV.